Women as a workforce in the organized sector : empirical perspectives - Singh, I. S., Dr.; Gandhi Labour Institute (New Delhi : Oxford & IBH Pub. Co., 1995)
Papers presented at Seminar on Women as a Workforce in the Organized Sector: Empirical Perspectives, held in Gandhi Labour Institute, during 28-29 Dec. 1991.
Includes bibliographical references and index.
Keywords: Women -- Employment -- India -- Congresses